Analysis of the Influence Mechanism of AIGC on the Evolution of Film Production Aesthetics and Visual Style - Yang, Siqi (Pinnacle Academic Press Proceedings Series, 2026)
As artificial intelligence technology becomes deeply integrated into film and television creation, artificial intelligence-generated content (AIGC) is reshaping the production paradigm of the film industry through algorithms such as deep learning and neural networks. This paper focuses on the profound impact of AIGC technology on film production aesthetics and visual style. First, it reviews the historical evolution of film production aesthetics and visual styles, outlining key stages in the transition from traditional photochemical workflows to digital and algorithmic image-making. Second, it analyzes the technical principles of AIGC and its main application scenarios in pre-production, production, and post-production, including script assistance, visual concept generation, virtual cinematography, and automated compositing. On this basis, the paper explores the mechanisms and methods by which AIGC influences film aesthetics, demonstrating how it promotes new forms of human–machine collaboration, reshapes the audience’s aesthetic experience, expands the expressive potential of visual elements, and deepens the integration of narrative and visual design. Furthermore, it discusses the challenges that film production faces in the AIGC era, including technological reliability, ethical responsibility, authorship and copyright, and the restructuring of professional roles and skills. By synthesizing these dimensions, the study provides a theoretical basis for understanding technology-driven transformations in film art and offers a reference for the film industry as it adapts to rapid advances in intelligent content generation.